Peripartum Cardiomyopathy: Challenges in Diagnostic and Management in Limited Resources Hospital in Kalabahi, Indonesia - Laurentius Andre; Tioky Sutjonong; I Nyoman Y. D. S. Barath (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Peripartum cardiomyopathy is a rare condition of heart failure between the last month of pregnancy and the first five months post-delivery. A 22 years old female G1P0A0 was experiencing dyspnea during her labor phase. Patient was assessed with PPCM and pulmonary edema based on her signs and symptoms of heart failure with no history of cardiac abnormalities, rales on both lungs, vascular congestion bilaterally, and left ventricle ejection fraction (LVEF) of 43%. Patient was managed with heart failure management including inotropes, furosemide, ACE inhibition, and on a mechanical ventilator. Patient was extubated, and inotropic and furosemide free on the sixth day of care, but redevelop pulmonary edema. Patient then reintubated, and inotrope and furosemide were recontinued. Patient was stable and extubated on the ninth day of care and discharged on the fifteenth day of care. The diagnosis and management of PPCM can be challenging especially in limited resources hospitals. Evaluation of the clinical characteristics of the patient are the keys of this management. Keyword: [peripartum cardiomyopathy, PPCM, pulmonary edema, limited resources hospital]